Feedback of Biomechanical Information for Japanese Elite Athletes - Ae, M.; Itoh, N.; Kintaka, H.; Sakamoto, T. (coachesinfo.com)
Although we all know that experiences and "rules of thumb" found in the field by athletes and coaches are one of the important factors in sports training, the effective and correct utilization of sport science information has become essential in optimizing the athlete's technique and improving performance. This is also true for recreational sportspersons. We have just moved into the stage of integrating sport science information and applying it to improvement in performance and the enrichment of life in sport. Scientific information is primarily used for the optimization and improvement of sports techniques. Figure 9 shows an example of the optimization of sports techniques and biomechanical motion database, which is based on our biomechanics feedback research. Compared with Figure 1, we emphasize the construction of a biomechanical motion database in which information is accumulated on motion patterns in the sports techniques of excellent athletes. Evaluation and diagnosis then occurs based on the database, and the application of computer simulation techniques. In the present system, we can compare the VTR images of the athlete with a model of standard motion from database or with expected motion patterns, which can be superimposed on the VTR images of the athlete, if necessary. In the near future, the process of quick on-field feedback with the development of appropriate devices will be usable and popular in various sports training situations and even in the field of education. However, it is scholastic coaches and applied researchers that can successfully provide feedback information for athletes who should have accurate knowledge about sports techniques.